ORGANIZATION OF TEACHING HISTOLOGY: FROM CONCEPT TO REALIZATION - Sulaeva, O. (World of Medicine and Biology, 2015)
Optimization of Learning Management during the learning of the such fundamental medical sciences as histology, is based on the assessment of the structure and needs of the target audience, use of appropriate methods to increase motivation to study basic subjects, arrangement of the independent and classroom work of students, selection of content and forms of teaching using interactive learning technologies, implementation of appropriate examination of students’ knowledge and skills.
Keywords: The process of learning; management; technology training